The distribution of income between persons - Champernowne, D. G. (Cambridge, England : University Press, 1973)
This book aims at supplying describing and chart the distributions of income and to measure their properties by numerical co-efficients.
Includes index.
osa 19/06/17
Loans
Keywords: Income; Income - mathematical models..; Income distributions; Wealth